The effect of a gluten-free diet in patients with autoimmune thyroiditis, type 1 diabetes mellitus, psoriasis, metabolic syndrome and without gluten-related disorder - a literature review - Zaliwska, Dominika; Kraszkiewicz, Adrianna; Kienanh Do, Monika; Paduszyńska, Natalia; Gonciarz, Marta Justyna; Adamiec, Dominika Karolina; Strojny, Agnieszka Aleksandra; Dąbrowska, Anna; Kamińska, Monika Anna; Czach, Magdalena (Quality in Sport, 2024)
Introduction and aim of the study: The growing awareness of gluten-related disorders has led to widespread misinformation about the gluten-free diet(GFD). The potential benefits of removing gluten are not well evaluated, yet it is often recommended or self-implemented by patients without robust supporting evidence. This paper aims to determine whether eliminating gluten from the diet provides proven benefits for individuals with specific diseases, including autoimmune thyroiditis (AIT), type 1 diabetes (T1D), psoriasis, and metabolic syndrome, who do not have a diagnosed gluten-related disorder. Description of the state of knowledge: Adhering to a gluten-free diet may benefit patients with AIT and T1D even without celiac disease, although there is no clear evidence that it alleviates AIT or T1D symptoms and the improvements are not significant enough to recommend it universally. Further research on humans is needed to explore the potential preventive effect of GFD on T1D risk and prolonging partial remission. For psoriasis, a GFD can be beneficial for patients with gluten-related antibodies, potentially reducing or clearing skin lesions, but it shows no benefit for those without these antibodies. The data on the GFD's impact on cardiovascular disease remains contradictory and unreliable. Conclusion: For psoriasis patients who test positive for gluten-related antibodies, a gluten-free diet can be recommended. Current studies do not substantiate the necessity for patients with AIT, T1D or metabolic syndrome to completely eliminate gluten from their diet.